2019
DOI: 10.3928/02793695-20181023-03
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Grief Disorder and Its Relationship With Perceived Social Support and Depression Among University Students

Abstract: The purpose of the current study was to examine the association between prolonged grief disorder, perceived social support, and severity of depression among Saudi Arabian university students after the death of a significant individual. A cross-sectional design was used to examine descriptive characteristics, correlational relationships, and statistical mean differences between male and female participants on prolonged grief disorder (PGD) scores in a convenience sample of Saudi Arabian college students. The Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
11
2
Order By: Relevance
“…Our participants cited inadequate supply of services as the primary difficulty encountered, with availability difficult to come by. This is unlike other studies in both adolescents and university students focusing on the quality of formal help services and the experiences of using them [51][52][53][54]. The barriers found in this study strongly suggest that there is also an issue with the quantity available, not just the quality of service and the user experience.…”
Section: Discussioncontrasting
confidence: 92%
“…Our participants cited inadequate supply of services as the primary difficulty encountered, with availability difficult to come by. This is unlike other studies in both adolescents and university students focusing on the quality of formal help services and the experiences of using them [51][52][53][54]. The barriers found in this study strongly suggest that there is also an issue with the quantity available, not just the quality of service and the user experience.…”
Section: Discussioncontrasting
confidence: 92%
“…Perceived social support refers to the degree to which individuals believe they have social support and the impression whether they are supported by their social network (Barrera, 1986;Kuru & Piyal, 2018). Perceived social support can reduce individuals' negative psychological characteristics (Al-Gamal, Bin Saeed, Victor, & Long, 2019;Jacobson, Lord, & Newman, 2017;Henry et al, 2019) and it has an important impact on individuals' physical and mental health (Graziano & Elbogen, 2017;Itzick, Kagan, & Tal-Katz, 2017;Sirois, Millings, & Hirsch, 2016). The social causality model indicates that lack of social support can lead to anxiety.…”
Section: Perceived Social Support and Fomomentioning
confidence: 99%
“…Congruently to these findings, perceived lack of social support has been shown to be associated with MDD after a social loss [ 49 ]. As an example, a study conducted with university students who had encountered a significant loss showed that participants with lower perceived social support had higher prolonged grief disorder and depression symptoms [ 50 ]. These studies highlight the importance of social bonds.…”
Section: Loss and Grief: How Are They Associated With Prolonged Grief And Depression?mentioning
confidence: 99%